PEMANFAATAN PERPUSTAKAAN SEKOLAH SEBAGAI SUMBER BELAJAR BAHASA INDONESIA DI MIN 4 KOTA MEDAN - Aidilla Syuaira, Geniza; Dhea Arsita; Laila Qodri; Naffa Qaila Dalimunthe; Said Hasian Simanjuntak (Journal of Community Devation, 2024)
The purpose of this study is to ascertain the benefits of using MIN 4 Medan's school library as a resource for learning Indonesian. The subjects of this qualitative descriptive study include students, instructors, and principals of schools in Indonesia. According to the study's findings, the school library model is used to make sure that students use the library as a learning resource to finish their tasks. This utilisation strategy seeks to influence students' reading-related attitudes and awareness. The presence of a school library, teacher and student interest, well-organized book collections, and conditional lesson plans are all supportive elements. Lack of library employees, a confusing library layout, requiring a lot of study time, and other issues are the obstacles.